Implementasi Kesehatan dan Keselamatan Kerja (K3) pada Peternakan Domba Garut PDP Arafah Cianjur - Aura Ginta Setia; Awa, Awa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Occupational safety and health (OHS) is an important aspect in creating a good environment. However, workplace accidents often occur due to inadequate equipment. PDP Arafah Cianjur, a company engaged in food processing and distribution, is required to implement OHS optimally to reduce occupational accidents (KK) and occupational diseases (PAK) to create a safe, healthy, and productive work environment. The study aims to identify OHS problems that occur at PDP Arafah Cianjur, analyze the problem-solving efforts that have been undertaken by the company, and provide solutions to improve the OHS program. The method used is qualitative through direct observation and interviews. The results of the study indicate that the implementation of OHS at PDP Arafah Cianjur is not optimal. Problems were found in two main indicators, namely the environment and equipment. Several obstacles that emerged included a lack of worker discipline in following OHS procedures, a work environment that did not fully meet safety standards, and equipment maintenance that was not carried out regularly. These conditions have an impact on increasing the risk of KK and PAK and decreasing productivity. Problem solving; indicators of the condition of the work environment include rearranging the pen area and worker activity paths that were previously not well organized. Indicators of work equipment usage indicate the need to improve the use and maintenance of work equipment that is still simple and does not meet safety standards.